Utilization of SDS-PAGE (Sodium Dodecyl Sulfate-Polyacrylamide Gel) Electrophoresis in Protein Purification - Jumrah, Elfira; Sudding, Sudding; Amalia Luqman, Alya; Zachrina, Dwiny; Khairunnisa, Rifqiani; Hardiyanti, Sri; Dwi Gladinda, Virginia (Hayyan Journal, 2024)
A protein can be identified based on each level of its structure. Every protein contains at least primary, secondary and tertiary structures. Only a few proteins have a quaternary structure as well. The primary structure consists of a linear chain of amino acids. One of the electric field-mediated separation methods that is often applied to analyze proteins based on their size is SDS-PAGE electrophoresis. This technique is based on the assumption that after denaturation, the polypeptide chains covered in SDS micelles have comparable surface charge densities, so that the resulting differences in electrical migration are based on their size. SDS-PAGE separates protein molecules based on their particle size and shape. This gel can be made with varying pore sizes which are determined based on the total amount of acrylamide compound added (gel concentration). The gel pore size will become smaller as the gel concentration increases so that only protein molecules that have a small molecular weight can pass through. This measure of the molecular weight of a protein is useful in mapping proteins (protein profiling). The gel staining used is bromophenol blue which functions to color proteins because it binds weakly to proteins. The higher the protein concentration of a sample being electrophoresed, the resulting band will appear clear and thick. However, if the protein concentration of a protein is low, the resulting band will appear thin.